Persistent effect of organic matter pulse on a sandy soil of semiarid Patagonia - Gonzalez Polo, Marina (2015)
Studies of degraded semiarid regions have shown that organic residue addition is a sound restoration alternative. We examined the effects of a single dose (40 Mg ha−1) of biosolids compost (BC) and compost of the organic fraction of municipal solid waste (MC) 6 years after they were applied to a sandy soil of NW Patagonia. Results were compared with those of inorganic fertilization (IF, 100 kg N+35 kg P ha−1) treatment and of unamended control. We measured plant cover, biomass, and diversity and chemical, biological, and biochemical soil properties. We did not find any significant effect of treatments on plant attributes. However, effects on soil properties were significant and more persistent with composts than with IF, especially with BC, which had higher organic C and nutrients than MC. Total soil C and N were twice as high in the BC-amended soil as in the control and IF soils. Soil extractable P was 4-fold and 2-fold higher in BCandMC-treated soils, respectively, than in the control soil, and even higher than in the IF treatment in response to BC. The highest β-glucosidase and acid hosphomonoesterase activities were found in the BC-treated soil, related to higher C and P in the soil and to higher activities of both enzymes in the biosolids compost. The highest phenol oxidase activity was found in MC and in the MC-treated soil. Potential respiration and K2SO4-extractable C were higher in the compost-treated soil, but there was no difference in microbial biomass C between the compost-treated and the control soils. Despite the fact that the soil was coarse textured and a single moderate dose of compost was applied, recovery of soil chemical, microbiological, and biochemical properties was long-lasting, indicating that application of urban compost is a feasible restoration practice in this semiarid region.